2004
DOI: 10.1038/sj.ijo.0802606
|View full text |Cite
|
Sign up to set email alerts
|

BMI and waist circumference as predictors of lifetime colon cancer risk in Framingham Study adults

Abstract: BACKGROUND: It is unclear whether the increased risk of colon cancer associated with obesity differs for men and women, by distribution of body fat, or by location of the tumor. The primary goal of this study was to address these questions. METHODS: Eligible subjects from the Framingham Study cohort were classified according to body mass index (BMI) and waist size during two age periods: 30-54 y (n ¼ 3764) and 55-79 y (n ¼ 3802). All eligible men and women were cancer-free at baseline and had complete informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
208
4
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(243 citation statements)
references
References 44 publications
20
208
4
11
Order By: Relevance
“…Similar to what has been observed for the association between BMI and colon cancer 24,27,34 , when we stratified by gender, we found that a high BMI was associated with adenoma recurrence in men, but not women. A separate analysis for waist circumference did not appreciably alter the direction or magnitude of the association between BMI category and odds of recurrence.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to what has been observed for the association between BMI and colon cancer 24,27,34 , when we stratified by gender, we found that a high BMI was associated with adenoma recurrence in men, but not women. A separate analysis for waist circumference did not appreciably alter the direction or magnitude of the association between BMI category and odds of recurrence.…”
Section: Discussionsupporting
confidence: 88%
“…The evidence for obesity as a common risk factor in a number of human diseases, including colorectal cancer, has led to the hypothesis that the metabolic changes associated with chronic overeating and sedentary behaviors have a role in development of many pathologies 8 . The majority of epidemiologic studies support a role for obesity as a risk factor for colorectal adenomas [9][10][11][12][13][14][15][16][17][18] , cancers 12,[19][20][21][22][23][24][25][26][27][28][29][30] ; and colon cancer mortality 31,32 . These observations suggest a continuous action of the adverse effects of obesity along the adenoma to carcinoma continuum, starting early in colon tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also did not have individuallevel socioeconomic data such as income, poverty, education, or insurance status, nor did we have any information regarding any of the individual health behaviors or risk factors (smoking, diet, exercise, etc) associated with CRC incidence and morbidity. [90][91][92] We also did not control for migration patterns or county-level demographic trends. For example, if welleducated, well-insured African American individuals moved en masse into a county in which they were poorly represented in the past, it could create the appearance of a county that has improving health outcomes rather than the simple in-migration of individuals more likely to have better outcomes.…”
Section: Limitationsmentioning
confidence: 99%
“…El advenimiento de la obesidad trae un aumento del conjunto de riesgos para las otras patologías crónicas como diabetes, hipertensión arterial, depresión y neoplasias múltiples 4 . Sus características destacadas son el aumento de la adiposidad localizada en la región abdominal o generalizada 5 .…”
Section: Introductionunclassified